THE EXISTENCE OF CUSTOMARY INHERITANCE LAW NORM DEVELOPMENT IN JURISPRUDENCE SUPREME COURT - Poespasari, Dr. Ellyne Dwi; Erlangga, Afga Samudera; Soelistyowati, Dr. (jfpublisher, 2023)
Customary inheritance law is affected by three kinship systems, which are patrilineal kinship, matrilineal kinship and parental kinship. These three kinship systems have their own characteristics that are typically traditional ones. Traditional customary inheritance law norms in the patrilineal kinship system explain that only male descendants are heirs in the distribution of their parents' inheritance. Meanwhile, women (daughters and widows) are not heirs of their parents/fathers or husbands. On the other hand, the norms of traditional customary inheritance law in Minangkabau with a matrilineal kinship system, which is from the mother or female line, are basically male descendants and female descendants of their mother's property. The father's property is inherited by his sisters and nieces. The norms of inheritance law in the parental kinship system do not distinguish between the position of sons and daughters. Therefore, both sons and daughters have the same rights in the distribution of inheritance from their parents. The development of customary inheritance law norms can be affected by the decisions of judges or the jurisprudence of the Supreme Court. The research method used normative legal research, which refers to legal norms regulated in laws and regulations, literature, expert opinions in order for the researchers to obtain information related to legal issues. Normative legal research is legal research conducted by examining literature or secondary legal materials as basic material to be researched by conducting searches of regulations, jurisprudence or judges' decisions and literature related to the issues discussed.